Sosialisasi Story Telling dan Media Poster untuk Menumbuhkan Minat Baca pada Anak Usia Dini di Desa Tanjung Dalam - Dhea Wandira (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The community service program in the form of education which is carried out on the basis of the collaboration of students from the Raden Fatah State Islamic University Palembang Real Work Study Program with Tanjung Dalam Village, Rambang District, Muara Enim Regency, South Sumatra Province provides teaching related to the introduction of storytelling as a means of fostering interest in reading in young children early through the media posters. The formation of children's behavior must at least form habits from an early age. This is important because early age is the initial stage of human life. Posters as learning can function to attract children's interest in the message to be conveyed, seek support for an event or idea, and make children interested in the information displayed and carry out the messages displayed on the poster. Research methods carried out by the author in implementing this KKN is with a qualitative research approach which is a method that is more often done when going directly to the field. Through this activity it is hoped that children will know and learn about storytelling and will be interested in reading books and other reading materials whose stories have been conveyed in storytelling or storytelling activities. Thus, the public's interest in reading, especially early childhood, will increase.